2020
DOI: 10.1111/bph.15179
|View full text |Cite
|
Sign up to set email alerts
|

A marine fungus‐derived nitrobenzoyl sesquiterpenoid suppresses receptor activator of NF‐κB ligand‐induced osteoclastogenesis and inflammatory bone destruction

Abstract: Background and Purpose: Osteoclasts are unique cells to absorb bone. Targeting osteoclast differentiation is a therapeutic strategy for osteolytic diseases. Natural marine products have already become important sources of new drugs. The naturally occurring nitrobenzoyl sesquiterpenoids first identified from marine fungi in 1998 are bioactive compounds with a special structure, but their pharmacological functions are largely unknown. Here, we investigated six marine fungus-derived nitrobenzoyl sesquiterpenoids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 61 publications
3
47
0
Order By: Relevance
“…However, our data showed that insulicolide A had no significant reduction on p65 of NF-κB and the phosphorylation of ERK, p38, and JNK of MAPKs, which were incompletely consistent with the effects of NS4 (structural isomer of insulicolide A) on NF-κB. NS4 exhibited inhibitory effects on NF-κB by binding with NF-κB p65 Arg B246 ( Tan et al, 2020 ), the different mechanisms between NS4 and insulicolide A on NF-κB may be due to their different conformations and their affinity with NF-κB. These results suggested that NF-κB and MAPKs might not be a downstream signal by insulicolide A to treat RANKL-induced osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…However, our data showed that insulicolide A had no significant reduction on p65 of NF-κB and the phosphorylation of ERK, p38, and JNK of MAPKs, which were incompletely consistent with the effects of NS4 (structural isomer of insulicolide A) on NF-κB. NS4 exhibited inhibitory effects on NF-κB by binding with NF-κB p65 Arg B246 ( Tan et al, 2020 ), the different mechanisms between NS4 and insulicolide A on NF-κB may be due to their different conformations and their affinity with NF-κB. These results suggested that NF-κB and MAPKs might not be a downstream signal by insulicolide A to treat RANKL-induced osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 57%
“…C-Fos knockout mice showed decreased NFATc1 nuclear translocation and severe bone sclerosis ( Matsuo et al, 2004 ). Here, our findings determined that the nuclear protein level of c-Fos was drastically inhibited by insulicolide A in the BMMs of RANKL stimulation, which was also different with NS4, while NS4 had little effect on c-Fos nuclear expression during RANKL-induced osteoclast formation ( Tan et al, 2020 ). Thus, the decrease in RANKL-induced c-Fos activation and the following attenuated NFATc1 nuclear protein levels, contributes to impaired osteoclastogenesis after insulicolide A treatment.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…AChE inhibitory activity was evaluated in vitro according to the modified Ellman method [ 25 ]. Briefly, 0.1 U/mL AChE solution was prepared by dissolving in phosphate buffer (pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
“…The differentiation of the osteoclast is modulated by two critical factors, the macrophage colony stimulation factor (M-CSF) and the receptor activator of the nuclear factor kappa-B (NF-κB) ligand (RANKL). RANKL signaling pathways have been recently proposed as key targets for inhibiting osteoclast differentiation and bone resorption [ 4 ]. Hence, many efforts have been recently devoted to the discovery of lead compounds from natural sources that target RANKL-induced osteoclast differentiation for attenuating enhanced bone resorption and bone loss [ 5 ].…”
Section: Introductionmentioning
confidence: 99%